THE RELATIONSHIP BETWEEN THE PROHIBITION OF REFOULEMENT AND THE PROHIBITION OF COLLECTIVE EXPULSION IN THE CONTEXT OF ACCESS TO TERRITORY: STANDARDS OF THE EUROPEAN COURT OF HUMAN RIGHTS AND THEIR RELEVANCE FOR THE LEGAL SYSTEM OF THE REPUBLIC OF SERBIA - Cuckovic, Bojana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
This article examines the relationship between the prohibition of refoulement contained in Article 3 of the European Convention on Human Rights and the prohibition of collective expulsion of aliens guaranteed by Article 4 of Protocol No. 4. After identifying common and distinctive elements of the two provisions, the author tests the main hypothesis that the prohibition of refoulement and the prohibition of collective expulsion are separate prohibitions with an independent existence, but that in the specific context of access to territory, they are intertwined in a variety of ways. The analysis has led to the conclusion that, despite the open questions that remain, the linkage between the two provisions can be used for corrective purposes, particularly in light of the recent lowering of standards by the ECtHR in relation to the prohibition of collective expulsion. It is also suggested that the difference between the positive obligations contained in the two ECHR articles has no significance for the authorities acting on the ground. As the protection afforded by the two prohibitions is complementary, national authorities must ensure that both border practices at and outside the means of legal entry comply with the ECHR standards in relation to both provisions.
Keywords: refoulement; collective expulsion of aliens; access to territory; European Court of Human Rights; means of legal entry; border practices; Serbia